Population pharmacokinetic study in children with vascular anomalies: body weight as a key variable in predicting the initial dose and dosing frequency of sirolimus - Fan, Lin; Guo, Hong-Li; Zhao, Yue-Tao; Li, Yue; Wang, Wei-Jun; Huang, Jian; Hu, Ya-Hui; Zou, Ji-Jun; Chen, Feng (Frontiers in Pharmacology, 2024)
The main challenges faced when using sirolimus in children with vascular anomalies (VAs) still include significant pharmacokinetic (PK) variability, uncertainty in the target concentration range, as well as inconsistencies in initial dosing and dosing frequency. The aim of this study is to establish a new population pharmacokinetic (PPK) model for children with VAs to guide the individualized use of sirolimus.Methods: A PPK study was performed using data from children with VAs who received sirolimus between July 2017 and April 2022. A nonlinear mixed-effect modeling with a one-compartment model structure was applied. Monte Carlo simulation was employed to propose specific dosing recommendations to achieve the target trough concentrations (Ctrough) of 5-15 ng/mL.In total, 134 blood concentrations from 49 pediatric patients were used to characterize the sirolimus pharmacokinetics. Covariate analysis identified body weight (BW) as a significant factor affecting clearance (CL) in the final PPK model. The typical clearance rate and distribution volume, standardized to a BW of 16 kg, were 4.06 L/h (4% relative standard error, RSE) and 155 L (26% RSE), respectively. Optimal dosing regimens were simulated for different BWs. For a twice-daily regimen, the recommended doses were 0.05, 0.06, 0.07, and 0.08 mg/kg/day for BW of < 10, 10-20, 20-40, and ≥ 40 kg, respectively; for a once-daily regimen, the recommended doses were 0.06, 0.07, 0.08, and 0.09 mg/kg/day for BW of < 10, 10-30, 30-50, and ≥ 50kg, respectively. Notably, sirolimus Ctrough could be maintained between 5-15 ng/mL across various dosing frequencies based on the recommended dosing regimen.We established a PPK model of sirolimus for children with VAs and proposed an initial dosing strategy. Integrating initial dose and medication frequency recommendations into sirolimus' guidelines will broaden its clinical options and simplify the clinical management for childhood VAs.